Clinical Course and Treatment Response of Neuromyelitis Optica Spectrum Disease: An 8-Year Experience. Issue 3 (May 2019) - Lin, Chao-Wen; Lin, I-Hung; Chen, Ta-Ching; Jou, Jieh-Ren; Woung, Lin-Chung
Abstract : Purpose: To report the clinical course and treatment response in a cohort of patients with neuromyelitis optica spectrum disorder (NMOSD) from a single referral center in Taiwan. Design: Case series. Methods: All NMOSD patients who received treatment and follow-up checks at National Taiwan University Hospital for at least 2 years between January 2008 and December 2016 were recruited. Demographic data and detailed characteristics of clinical course including acute episodes, maintenance therapies, and visual outcome were collected. Patients were examined every 6 months and during each episode of relapse. Results: A total of 96 patients were identified; of them, 68 (70.8%) had optic neuritis. Optic neuritis was the initial presentation of NMOSD in 44 patients. Among the patients with optic neuritis, 32.4% had recurrent optic neuritis within 1 year from the first episode. Compared with the group without optic neuritis, the group with optic neuritis had a younger age of presentation (34.4 ± 15.9 vs 42.4 ± 14.8 years, P = 0.02) and a higher 1-year recurrence rate (64.7% vs 17.9%, P < 0.001). Among the patients with optic neuritis, 51.5% had a final visual acuity of worse than 20/200. Multiple regression analysis showed that the presence of aquaporin-4-IgG antibodies and poor initial visual acuity were the risk factors for worse visual outcome. Conclusions: In this study, patients with optic neuritis were younger and had a higher 1-year recurrence rate. Despite using steroid therapy during the acute phase and immunosuppressive agents as long-term treatment, visual prognosis was poor. Aquaporin-4-IgG antibodies and initial visual acuity were associated with final visual outcome.